2016
DOI: 10.1116/1.4961113
|View full text |Cite
|
Sign up to set email alerts
|

Hardness, elastic modulus, and wear resistance of hafnium oxide-based films grown by atomic layer deposition

Abstract: The investigation of mechanical properties of atomic layer deposition HfO 2 films is important for implementing these layers in microdevices. The mechanical properties of films change as a function of composition and structure, which accordingly vary with deposition temperature and post-annealing. This work describes elastic modulus, hardness, and wear resistance of as-grown and annealed HfO 2. From nanoindentation measurements, the elastic modulus and hardness remained relatively stable in the range of 163-16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…We again note the extremely low value of 74 ± 1 GPa reported by Ilic for a 21 nm ALD HfO 2 film 61 indicated a mass density of 6.1 ± 0.1 g/cm 3 , substantially reduced relative to the values of 9.7-9.8 g/cm 3 reported for the other ALD HfO 2 films with considerably higher Young's modulus values. 60,251,252 This may be related to the extremely small thickness for the Ilic HfO 2 film relative to the other studies (60-200 nm). Even so, Zizka 253 determined a substantially higher density (9.8 g/cm 3 ) and modulus (166 ± 10 GPa) for an ALD HfO 2 film of similar thickness.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…We again note the extremely low value of 74 ± 1 GPa reported by Ilic for a 21 nm ALD HfO 2 film 61 indicated a mass density of 6.1 ± 0.1 g/cm 3 , substantially reduced relative to the values of 9.7-9.8 g/cm 3 reported for the other ALD HfO 2 films with considerably higher Young's modulus values. 60,251,252 This may be related to the extremely small thickness for the Ilic HfO 2 film relative to the other studies (60-200 nm). Even so, Zizka 253 determined a substantially higher density (9.8 g/cm 3 ) and modulus (166 ± 10 GPa) for an ALD HfO 2 film of similar thickness.…”
mentioning
confidence: 80%
“…• C. 251 Thus, while the measured CTE values can be reasonably explained by literature precedent, the grain orientation (or lack of orientation) in ALD HfO 2 films is likely highly dependent on the film thickness and specific growth conditions. This of course neglects the possible presence of anisotropy in the Young's modulus of the ALD HfO 2 film.…”
Section: 290mentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, Tapily et al [37] showed that the atomic layer deposition (ALD) method leads to the formation of HfO 2 film with a hardness and elastic modulus equal 9.5 and 220 GPa, respectively. Moreover, Berdova et al [58] showed that in the ALD method, there is a direct impact of the deposition temperature on the mechanical properties of the HfO 2 thin films. The hardness and elastic modulus were slightly reduced in a function of the growing deposition temperature from 9.7 to 8.3 GPa, and 165 to 163 GPa, respectively [58].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Moreover, Berdova et al [58] showed that in the ALD method, there is a direct impact of the deposition temperature on the mechanical properties of the HfO2 thin films. The hardness and elastic modulus were slightly reduced in a function of the growing deposition temperature from 9.7 to 8.3 GPa, and 165 to 163 GPa, respectively [58]. Leyland and Matthews [59] proved that in the classical theory of wear, hardness is the primary material property that defines wear resistance.…”
Section: Mechanical Propertiesmentioning
confidence: 99%